Chapter 30 The Role of Participants in Online Privacy Research Ethical and Practical Considerations - Breuer, Johannes (Taylor & Francis, 2023)
Online privacy research considers the determinants, dimensions, and consequences of information disclosure on the internet. In this endeavor, researchers often are interested in uncovering personal and potentially sensitive details about media use and (privacy-related) attitudes and behavior. This focus raises a number of ethical questions that researchers need to address. Ethical questions relate to issues of data protection, but also to other topics, such as the role of study participants. Digital trace data have become increasingly popular in the social and behavioral sciences in recent years and constitute a promising resource for online privacy research. While digital trace data come with their own set of challenges that may increase specific ethical concerns, they also hold the potential for innovation in research design, for the involvement of study participants, and for more research transparency. In this chapter, we discuss ethical challenges in online privacy research, with a particular focus on the role of participants, and illustrate how digital trace data - and their combination with other types of data - can be used to find and develop novel approaches for online privacy research that also consider key ethical questions.